Thomson scattering measurement of a collimated plasma jet generated by a high-power laser system. (March 2016) - Ishikawa, T.; Sakawa, Y.; Morita, T.; Yamaura, Y.; Kuramitsu, Y.; Moritaka, T.; Sano, T.; Shimoda, R.; Tomita, K.; Uchino, K.; Matsukiyo, S.; Mizuta, A.; et al.
Abstract: One of the important and interesting problems in astrophysics and plasma physics is collimation of plasma jets. The collimation mechanism, which causes a plasma flow to propagate a long distance, has not been understood in detail. We have been investigating a model experiment to simulate astrophysical plasma jets with an external magnetic field [Nishio et al., EPJ. Web of Conferences 59, 15005 (2013)]. The experiment was performed by using Gekko XII HIPER laser system at Institute of Laser Engineering, Osaka University. We shot CH plane targets (3 mm × 3 mm × 10 μ m) and observed rear-side plasma flows. A collimated plasma flow or plasma jet was generated by separating focal spots of laser beams. In this report, we measured plasma jet structure without an external magnetic field with shadowgraphy, and simultaneously measured the local parameters of the plasma jet, i.e., electron density, electron and ion temperatures, charge state, and drift velocity, with collective Thomson scattering.